A Symptom Profile Analysis of Depression in a Sample of Iranian Patients - Shekoofeh Seifsafari; Ali Firoozabadi; Ahmad Ghanizadeh; Alireza Salehi (Iranian Journal of Medical Sciences, 2013)
Background: In some cultures, including ours, direct explanation of inner psychic world is inhibited and stigmatized, therefore finding alternative modes of expression. The aim of this cross-sectional study was to assess the frequency of somatization in the depressed patients.Methods: The present study comprised 500 patients referred to the outpatient clinic of Shiraz University of Medical Sciences, and diagnosed with major depressive disorders based on DSM-IV-TR. The presenting complaints of these patients were assessed through psychiatric interview. The presenting symptoms were divided into three main categories including mental symptoms, pain, and physical symptoms without pain. Statistical analysis (chi-square and logistic regression) were performed to determine the relationship between presenting symptoms and some demographic variables such as age, gender, marital status, educational level and cultural background (urban or rural).Results: Physical symptoms other than pain, mental symptoms, and pain were found in 193 (38.6%), 186 (37.2%), and in 121 (24.2%) patients respectively. Pain and physical complaints were more common in patients with rural cultural background, lower education, women and the married individuals. Headache (15.2%), irritability (10.6%) and pain in different parts of the body (10.4%) were the most frequent chief complaints of the patients. Hypochondriasis, suicidal idea, crying, irritability and insomnia were significant symptoms associated with the complaint of somatization.Conclusion: Somatic symptoms, especially pain, have a significant weight in the chief complaints of depressed patients. Physicians need to pay particular attention to this important issue in order to better understand these patients.